2005
DOI: 10.1371/journal.pmed.0020172
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Unexpected Late Fetal Death in Monochorionic Twins Despite Intensive Ultrasound Surveillance: A Cohort Study

Abstract: BackgroundThe rationale for fetal surveillance in monochorionic twin pregnancies is timely intervention to prevent the increased fetal/perinatal morbidity and mortality attributed to twin–twin transfusion syndrome and intrauterine growth restriction. We investigated the residual risk of fetal death after viability in otherwise uncomplicated monochorionic diamniotic twin pregnancies.Methods and FindingsWe searched an electronic database of 480 completed monochorionic pregnancies that underwent fortnightly ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
5
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 38 publications
6
114
5
8
Order By: Relevance
“…Therefore, early diagnosis of chorionicity is vital in twine or multiple pregnancies [6]. So, procedures have been suggested in precise monitoring of fetuses in monochorionic twin pregnancies to prevent morbidity and mortality [4,9,[11][12][13]. It should be noted, however, none of these pathologic entities were present, neither in the study by Ingec et al, nor in the present study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Therefore, early diagnosis of chorionicity is vital in twine or multiple pregnancies [6]. So, procedures have been suggested in precise monitoring of fetuses in monochorionic twin pregnancies to prevent morbidity and mortality [4,9,[11][12][13]. It should be noted, however, none of these pathologic entities were present, neither in the study by Ingec et al, nor in the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…The determination of chorionicity is important for predicting the prognosis of pregnancy, because it has been shown that in monochorionic cases, vascular anastomoses or imbalanced placental vascular distribution in the two placentas may lead into the twin insufficiency syndrome. In addition, hemodynamic imbalances may jeopardize the health of both fetuses and cause significant consequences [4,9,10]. A worse prognosis in monochorionic pregnancies is possibly due to the twin to twin transfusion syndrome, growth restriction, and the twin reverse arterial perfusion syndrome in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…MZ twinning is an intrinsic feature of human reproduction. Because of the many disadvantages of MC placentation [Barigye et al, 2005], it is not clear what the evolutionary advantage of MZ twinning might be. It may merely be a phenocopy of DZ twinning, whose advantage would be a more rapid recovery per completed pregnancy following population loss through war, famine or disease.…”
Section: Mz Twinning Is Not a Random Teratogenic Eventmentioning
confidence: 99%
“…A pesar de la falta de evidencia de esto, la recomendación ha sido aceptada por el Real Colegio de Obstetricia y Ginecología (21). Por otra parte, esta indicación no debe ser considerada tan extraña, pues existen estudios que reportan que los gemelares monocoriales biamnióticos, sin signos ecográficos de transfusión feto fetal, tienen una tasa de muerte fetal entre las 28 y 36 (promedio 34) semanas de hasta un 5% (22), lo que justificaría aún más una interrupción electiva a las 34-35 semanas en casos de STFF tratados por fetoscopia.…”
Section: Discussionunclassified